Terminology and Ad hoc Interpreters in Public Services. An Empirical Study - Valero-Garcés, Carmen (The Journal of Specialised Translation, 2005)
Terminology is part of our lives. It is found in every written document from specialised texts addressed to experts, to any written piece addressed to the general public. It can also be found in oral texts and it is common in mass media. In the following pages, I will concentrate on the use of terminology and specialised language in a specific setting with specific participants: communication with the immigrant population in medical consultations through an interpreter. The main objective is twofold: First, to analyse the use of terminology in public services; secondly, to analyse the difficulties encountered and the strategies used by the interpreters in doctor-immigrant patient interviews dealing with specialised medical language. Finally, some conclusions will be drawn regarding the role of terminology in public services interpreting.